Presentation Variables Associated With the Development of Severe Post-obstructive Diuresis in Male Cats Following Relief of Urethral Obstruction - Muller, Kelly M.; Burkitt-Creedon, Jamie M.; Epstein, Steven E. (Frontiers in Veterinary Science, 2022)
Background: Diuresis following relief of urethral obstruction is a potentially life-threatening complication of feline urethral obstruction. Evidence regarding the incidence of post-obstructive diuresis (POD) in cats is scarce. Establishing historical, physical examination, and initial clinicopathologic variables associated with risk for developing POD may better enable clinicians to direct treatment for this common feline emergency and to educate clients regarding clinical and financial expectations. Objectives: To report the incidence of POD in a large group of cats with urethral obstruction and determine whether select presenting physical examination or initial clinicopathologic variables may predict the onset or severity of POD. Methods: The records of 260 cats that were admitted to the UC Davis Veterinary Medical Teaching Hospital for urethral obstruction were reviewed. Urine output after urethral catherization was categorized into no POD (urine output ≤ 2mL/kg/hour), mild-moderate POD (urine output > 2 but < 5 mL/kg/hour) and severe POD (urine output ≥ 5 mL/kg/hour). Select presentation physical examination, venous acid-base and electrolyte panel, serum biochemistry panel, and urinalysis results were compared among the groups. Results: 67.7% of cats experienced POD, and in 35% of cats it was categorized as severe. The historical and physical examination variables correlated with development of POD were lower body weight and, for severe POD, hypovolemia. Clinicopathologic variables associated with development of POD included acidemia, azotemia, hyperphosphatemia, hyperkalemia, hyponatremia, hypochloremia, hypocalcemia, hypermagnesemia, and hypoalbuminemia. Cats with severe POD were hospitalized a median of 1 day longer than those without. Conclusions: Results of the present study indicate that there are presentation variables associated with onset and severity of POD following relief of feline urethral obstruction.